Analisis Penerapan Prinsip Penyajian dan Pengungkapan (PPP) Standar Akuntansi Keuangan Kombinasi Bisnis di Laporan Keuangan PT GoTo Gojek Tokopedia Tbk (Jurnal Kendali Akuntansi, 2024)
Financial Accounting Standards (SAK) are guidelines for the preparation of corporate financial statements in Indonesia. There is a component of the Financial Accounting Standards that has an important role in business combination is the Presentation and Disclosure Principle (PPP) in the Financial Accounting Standards. A business combination occurs when one or more companies merge to form a new business entity separate from the merging companies. The method used in this research is descriptive analysis through the development of data related to the topic of discussion collected by reviewing the financial statements of PT GoTo Gojek Tokopedia Tbk which can be accessed on the Indonesia Stock Exchange (IDX) website. The result of this study is that PT GoTo Gojek Tokopedia Tbk has carried out business combination activities by identifying the party to be acquired and measuring the value based on a predetermined acquisition price in obtaining control in accordance with the percentage of ownership. This study aims to explain the application of business combination accounting based on PSAK 22 at PT GoTo Gojek Tokopedia Tbk. This research is intended as an effort to develop the knowledge obtained by the author in order to obtain an optimal solution in exploring the combination operation process carried out by PT GoTo Gojek Tokopedia Tbk.